Steaming towards a cyber secure shipboard navigation systems: a review of industry readiness - Ntuli, Samkelisiwe (Department of Commercial Law, 2025)
The increasing reliance on digital technologies in the maritime industry has led to a growing concern about cyber security. Shipboard navigation systems are particularly vulnerable to attack, as they are often connected to the 'internet of things' and contain sensitive data. This dissertation reviews the current state of cyber security in the maritime industry, and assesses the readiness of the industry to address this challenge. It is argued that there is a lack of awareness among maritime stakeholders of cyber security risks specifically to shipboard navigation systems, and that there is a need for improvement in security measures to be implemented to protect these systems to ensure the safety of maritime operations